Social action dialectic and social integration: An analysis of value rationality in the Grebeg Suro Giri Kusuma Tradition - Supriyanto, Agung; Falaq, Yusuf (Universitas Muhammadiyah Malang, 2026)
This study examines the persistence of the Grebeg Suro Giri Kusuma tradition in Demak Regency as a sociological phenomenon within the context of modernization. The main issue addressed lies in the tension between the dominance of modern rationality and the continuity of traditional ritual practices, which are often perceived as obsolete. This research aims to analyze how the interaction of various types of social action contributes to the formation of social integration and the maintenance of social cohesion within the community. The study employs a descriptive qualitative approach using Max Weber’s theory of social action. Data were collected through participant observation, in-depth interviews, and documentation. The findings reveal that Grebeg Suro functions not merely as a form of cultural preservation, but also as a social arena where multiple orientations of action intersect. Value-oriented rational actions rooted in religious teachings interact with traditional and affective actions in shaping collective practices. Ritual elements such as the heirloom procession, tirto wening water, and the distribution of agricultural offerings serve as symbolic media for articulating spiritual identity while reinforcing social solidarity. Theoretically, this study contributes to cultural and social change discourse by demonstrating that social integration in transitional societies is not solely structurally determined but is constructed through the collective interpretation of social actions. The novelty of this research lies in its interpretation of ritual as a dynamic mechanism for sustaining social stability. Therefore, the Grebeg Suro tradition transforms individual values into collective forces that support the continuity of the local social structure. Penelitian ini menganalisis keberlanjutan tradisi Grebeg Suro Giri Kusuma di Kabupaten Demak sebagai fenomena sosiologis dalam konteks modernisasi. Fokus permasalahan terletak pada ketegangan antara dominasi rasionalitas modern dan keberlangsungan praktik ritual tradisional yang kerap dipandang tidak relevan. Penelitian ini bertujuan untuk mengkaji bagaimana interaksi berbagai tipe tindakan sosial berkontribusi dalam membentuk integrasi dan mempertahankan kohesi sosial masyarakat. Pendekatan yang digunakan adalah kualitatif deskriptif dengan kerangka teori tindakan sosial Max Weber. Data diperoleh melalui observasi partisipatif, wawancara mendalam, dan dokumentasi. Hasil penelitian menunjukkan bahwa Grebeg Suro tidak hanya berfungsi sebagai praktik pelestarian budaya, tetapi juga sebagai arena interaksi sosial yang mempertemukan berbagai orientasi tindakan. Tindakan rasional berorientasi nilai yang berakar pada ajaran religius berkelindan dengan tindakan tradisional dan afektif dalam membentuk praktik kolektif masyarakat. Unsur ritual seperti kirab pusaka, tirto wening, dan perebutan gunungan berperan sebagai medium simbolik dalam mengartikulasikan identitas spiritual sekaligus memperkuat solidaritas sosial. Secara teoretis, penelitian ini berkontribusi pada kajian budaya dan perubahan sosial dengan menunjukkan bahwa integrasi sosial dalam masyarakat transisional tidak semata bersifat struktural, melainkan dibentuk melalui pemaknaan kolektif atas tindakan sosial. Kebaruan penelitian ini terletak pada pemahaman ritual sebagai mekanisme dinamis dalam menjaga stabilitas sosial. Dengan demikian, tradisi Grebeg Suro mampu mentransformasikan nilai individual menjadi kekuatan kolektif yang menopang keberlanjutan struktur sosial masyarakat lokal.